Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Exploring the potential mechanisms of the Prunus mume-Prunella vulgaris herb pair in treating endometrial polyps based on network pharmacology and molecular docking - Wen Yan Zhang; Yuan Yuan; Li Fan; Guang Rong Huang; Shu Yu Pan; Jing Xiao (Molecular Genetics and Genomics, 2026)

Exploration of shared gene signatures and molecular mechanisms between psoriasis and COVID-19: evidence from transcriptome data - Rong-Jing Dong; Lu-Hui Yang; Yu-Ye Li; You-Wang Lu (Mammalian Genome, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Secondary forest succession shifts soil carbon priming from microbial to mineral control through dynamic microbe–mineral coupling - Panpan Wu; Jing Zhang; Xi'an Cai; Zhijian Mou; Yue Li; Wenjia Wu; Tengteng Li; Rong Mao; Zhanfeng Liu (Soil Biology and Biochemistry, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Ecological restoration of coastal wetlands shapes soil carbon pools and microbial carbon cycling functions in Bohai Bay, China - Mengtuo Wen; Qiulan Zhang; Yasong Li; Jing Rong; Shengwei Cao; Yaci Liu (Estuarine, Coastal and Shelf Science, 2026)

Autogenous dentin graft material promotes bone regeneration involving OPN/CD44-mediated BMSC recruitment - Xin Deng; Jianmin Zhuo; Yanyan Yang; Ziliang Zhou; Jing Li; Rong Rong; Weihong Chen; Jiashen Chen; Siwen Yu; Siyuan Chen; Lu He; Janak Lal Pathak; et al. (Chemical Engineering Journal, 2026)

Straw return regimes improve mollisol quality by reshaping microbial composition and metabolic profiles - Xinyuan Li; Yanhui Dou; Tingting Cui; Jing Xu; Yuxian Wang; Junqiang Wang; Rong Jiang; Shumin Sun; Guanghui Hu; Wanrong Gu (Applied Soil Ecology, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Characterization of CYP402C5 associated with field resistance to three neonicotinoids in Bemisia tabaci - Chao Wang; Rong Zhang; Jing Yang; Mingjiao Huang; Hantang Lu; Ying Zhang; Youjun Zhang; Junkai Li; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Electrostatically assembled gold nanocluster-enhanced porphyrinic metal-organic framework nanozymes for oxygen-boosted photodynamic therapy of hypoxic tumors - Ao He; Juan Zhou; Jing Zhu; Guojing Hong; Minglan Fan; Yuyan Bao; Rong Li; Manxiao Cheng; Xiang Ran (Journal of Photochemistry and Photobiology B: Biology, 2026)

Ni/Cu co-doped modified Bi2WO6 microsphere for enhanced photocatalytic reduction of CO2 toward CO - Xiaolong Cai; Baiquan Jing; Rong Li; Baowei Cao; Jinbo Cao; Yunhua Xu (Chemical Engineering Journal, 2026)

Aberrant Gamma Oscillations in Parkinson’s Disease - Bing-Yu Li; Ruo-Yu Li; Rong-Hua Hong; Yun-Ping Song; Ling-Jing Jin (Neuroscience Bulletin, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Na-rich Na3.2V1.9Fe0.1O2(PO4)2F cathode unlocks high energy density and wide-temperature operation in sodium-ion batteries - Qiang Fu; Qin He; Fangxiang Song; Keliang Wang; Jing Li; Xianquan Ao; Rong Li (Chemical Engineering Journal, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Indole metabolites produced by Lactobacillus acidophilus impedes bisphenol F- aryl hydrocarbon receptor interaction and ameliorates bisphenol F induced depression-like changes - Miaoyang Hu; Ayiguzaili Manglike; Xiaozhu Li; Jin Wei; Xinyu Lou; Jing Liu; Zhiru Tang; Weiping He; Guixiang Ji; Wenjuan Wang; Tengfei Ma; Rong Gao; et al. (Journal of Hazardous Materials, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Commentary: the TSP-1-CD47-integrin α4β1 axis—deciphering pathogenic mechanisms and therapeutic horizons in rheumatoid arthritis - Jie Guo; Feng-yi Mai; Xin-yu Li; Yu Liu; Jing-rong Liang; Xing-long Li; Chen-guang Li (Inflammation Research, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Non-volumetric phase transition of PNIPAM enables high-sensitivity temperature monitoring and photoelectric therapy for wound care - Jie Ding; Danni Hou; Yuan Tian; Rong Li; Yuyan Wang; Junzhong Jiang; Yucai Hu; Chengheng Wu; Dan Wei; Jing Sun; Zi Qiao; Hongsong Fan (Chemical Engineering Journal, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Design, synthesis, characterization and exploration of anti-HBV activity of matrine-adenine hybrids - Meng-Fan Xie; Zhou-Fei Zheng; Jing-Lei Wang; Rong-Tao Li; Zhi-Jun Zhang (Molecular Diversity, 2026)

Grass carp TMEM33 promotes GCRV replication by targeting MAVS for degradation and suppressing host antiviral immune response - Qian Wang; Zichao Peng; Rong Deng; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He; Jing Lu (Marine Life Science & Technology, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Two new menthane monoterpene derivatives isolated from Hypericum monogynum - Yan-Rong Zeng; Hong-Jin Ban; Jing-Yi Yin; Zhan Feng; Ya-Nan Li; Yan Liu; Xiao-Jiang Hao; Chun-Mao Yuan (Phytochemistry Letters, 2026)

Evaluation of near infrared spectroscopy for direct detection of common microplastics contamination in camel Milk powder - Chunxu WAN; Yin LIU; Jing XIE; Feng CHEN; Huijie SHEN; Rong LI (Food Chemistry, 2026)

Using integrated multi-omics and molecular docking to decode stone epiphytic culture as a strategy for enhancing flavonoids and bioactivity in Dendrobium officinale leaves for functional tea development - Jing Li; Rong Zhou; Yingyue Hou; Yichang Chen; Shaohao Xie; Jinyu Wu; Jiang Chen; Hongbin Hou; Guangying Du (Food Bioscience, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

Synergistic effects of polystyrene microplastics and 17α-methyltestosterone on immune and oxidative stress responses in the gill and liver of Gobiocypris rarus - Yibo Jia; Lu Cao; Tongyao Li; Haiyan Zhao; Gen Chen; Zijun Xiong; Weiya Rong; Qing Liu; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; et al. (Fish & Shellfish Immunology, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Silencing NRBP1 Gene with shRNA Improves Cognitive Function and Pathological Features in AD Rat Model - Xinxue Wei; Xiaobei Liu; Yunqing Ban; Jing Li; Rong Huang (Biochemical Genetics, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Mechanism study on ultrasonication combined with soybean 11S globulin to improve the quality and flavor compounds of low-salt lamb meat gel - Rong Bai; Hongqing Nie; Jing Xi; Aitmagambetova Madina; Lin Li; Huiyu Han; Shengqi Jiang; Gege Wang; Wu Ding (Meat Science, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Irradiation co-succinylation modification of caprine casein: Impact on physicochemical properties, molecular structure, and functional properties - Jing Xi; Huiyu Han; Rong Bai; Madina Aitmagambetova; Siying Wang; Shengqi Jiang; Hongqing Nie; Lin Li; Xiang Ye; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Development and Evaluation of Antioxidant Postbiotics from Bacillus amyloliquefaciens C-1 to Alleviate DSS-Induced Colitis - Xinyao Hou; Jiayu Feng; Jiale Qin; Jianhui Mo; Rong Yu; Jia Lv; Shaoru Li; Jing Tian; Yue Cheng; Bei Han (Probiotics and Antimicrobial Proteins, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Aquaporin-1 stabilizes β-catenin to promote NLRP3 inflammasome-mediated pyroptosis in rheumatoid arthritis - Meng-yuan Zhou; Zi-yao Gao; Jing Sun; Wen-cai Long; Juan Zhou; Wen-jing Fang; Xue-chun Wang; Sheng-dong Wu; Rong Li (Apoptosis, 2026)

Tailoring a simplified and steady-state kombucha consortium for newly-formulated kiwifruit beverage production: Impacts on untargeted/targeted metabolites, antioxidant capacities and flavor profiles - Shiqi Li; Keying Chu; Rong Guo; Jiamin Wu; Xingnan Wang; Jing Guo; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2026)

Ion−dipole−induced high stability of acidic DESs for efficient extractive and oxidative desulfurization - Dongao Zhu; Jie Yin; Siyi Han; Rong Zhang; Chunyan Dai; Jing He; Hongping Li; Wenshuai Zhu; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2026)

Robust copper/mesoporous silica catalyst for efficient furfural hydrogenation to furfuryl alcohol - Xin-Yu Xiao; Jie Zhang; Rong Wang; Qi Wang; Hai-Song Li; Jing-He Yang (Biomass and Bioenergy, 2026)

Assessing the impacts of climate and human activities on NDVI trends in Shanxi Province, a semiarid–semihumid region of China - Yujing Sun; Guoqiang Peng; Jing Li; Xiaogang Huang; Jia Rong (Remote Sensing Applications: Society and Environment, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

Research on decoupling and characterization methods of geological elements based on pre-stack seismic data - Cong Ren; Rong-rong Zhao; Ming-yi Li; Jing-jing Zong; Han-peng Cai; Wenhao Li (Applied Geophysics, 2025)

Distribution and potential drivers of methane emissions from deep-sea environments in Haima cold seep areas - Li Tang; Jing-Chun Feng; Can-Rong Li; Xiao Chen; Hui Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Introduction Tracing methane originating from deep-sea environments is essential for understanding the global methane budget. However, knowledge regarding the mechanisms governing methane transfer from deep-sea sediments to the water column in cold seep environments remains limited. This study aims to quantitatively investigate the distribution of methane and identify its controlling factors within the Haima cold seep areas. Methods A comprehensive analysis was conducted to investigate the distribution characteristics of methane and its potential drivers in both the water column and sediment porewaters within the Haima cold seep areas. Results The key findings are: (1) Haima cold seeps serve as a methane source to the atmosphere, with pronounced spatial heterogeneity in emission strength across the monitored regions. (2) The vertical distribution of methane is influenced by multiple environmental factors. Key factors in sediment porewaters include sediment depth, porosity, inorganic carbon (IC), chloride (Cl – ), and sulfate (SO 4 2– ), whereas silicate (SiO 3 2– ) and dissolved oxygen (DO) are primary regulators in the water column. (3) Sediments represent a significant methane source for bottom seawater, with methane consumption being more pronounced in seepage areas than in non-seepage areas. Discussion This study demonstrates that methane dynamics in the Haima cold seep are complex and driven by a combination of physical, chemical, and biological processes across the sediment–water interface. The identified key drivers underscore the importance of porewater geochemistry and water column biogeochemistry in controlling methane release. These findings significantly advance our understanding of methane transport in deep-sea seep systems and provide crucial insights for refining global methane flux estimates.

A review of data-driven key technologies for intelligent citrus systems - Wengang Li; Aoting Wan; Jing Li; Kelin Chen; Zifei Ma; Qinghua Li; Rong Jiang; Juan Yang; Tong Li (Computers and Electronics in Agriculture, 2025)

Regulatory mechanisms of total phosphorus on N2O concentrations: A case study of Dongting lake - Jie Liang; Yi Li; Weixiang Li; Ziqian Zhu; Xiang Gao; Ran Du; Lan Lu; Jing He; Chaozhong Tan; Rong Wu; Jikai Liao (Water Research, 2025)

Polarization electric field tuning interface electric field in full-spectral response double S-scheme heterojunction to drive synchronous removal of Cr(VI) and RBR X-3B - Jing Bai; Xiangling Zhang; Chen Wang; Xuhao Li; Shilong Cao; Rong Zhang; Jiezhou Hu (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Bi-mediated Z-scheme heterojunction of carbon-rich BiO2-X /Carbon nitride: Enabling a sensitive photoelectrochemical aptasensor for diazinon detection - Quan Shen; Rong Zhi; Song Zhang; Yi Ding; Jing Huang; Yuqi Chen; Keqiang Xu; Pengcheng Yan; Henan Li (Journal of Environmental Chemical Engineering, 2025)

Sources and formation characteristics of atmospheric water-soluble organic carbon in North China: Implications from a one-year background observation - Jing Yu; Rong Sun; Yuchen Li; Xuehua Yin; Zheng Zong; Ling Sun; Chongguo Tian (Atmospheric Environment, 2025)

Comprehensive study of W06A7.4 and TMEM144 mediated pathways in aging: insights from Caenorhabditis elegans to human - Li Fang Wang; Xiaorong Liu; Sisi Li; Rong Li; Ran Li; Fengxia Yan; Xi Jing (Molecular Genetics and Genomics, 2025)

Utilization of river and lake dredged sediments for growing medium Preparation and its effect on the growth of alfalfa and bermudagrass: Germination, growth, and feasibility analysis - Rong Zhang; Xiangling Zhang; Bi Wu; Chen Wang; Jing Bai; Xuhao Li; Lingwei Kong; Zhouying Xu; Shilong Cao; Xinlu Xiao (Journal of Soils and Sediments, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Concentration-dependent visual SO2 detection from trace to pure in a zirconium MOF - Guang-Rui Si; Xiang-Jing Kong; Lin-Hua Xie; You-Tuo Zhang; Tao He; Jian-Rong Li (Science Bulletin, 2025)

Clay-doped two-phase particle fracture sealing material: Sealing mechanism insights and molecular dynamics simulation - Wenhao Hou; Jianwei Cheng; Rong Chen; Marek Józef Borowski; Jiangtao Li; Jing Mei; Yifan Li (Process Safety and Environmental Protection, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Spatial distribution and chemical characteristics of bastnäsite and monazite provide insights into the Bayan Obo deposit, the world's largest rare earth element mineralization - Jin Wang; Lin Li; M. Santosh; Guo-Ying Yan; Jun-Feng Shen; Mao-Wen Yuan; Masroor Alam; Zhao-Jing Wang; Sheng-Rong Li (Lithos, 2025)

Optimizing CH4 recovery and CO2 sequestration in natural gas hydrate exploitation through dynamic adjustment of CO2/N2 injection composition: A simulation study - Jing-Yu Kan; Jian Kang; Jun-Rong Qin; Xing Huang; Nan Li; Zhi Li; Guang-Jin Chen (Fuel, 2025)

Z-scheme heterojunction engineered covalent organic polymer for thermodynamically optimized CO2 photoreduction - Jiaxin Rong; Xuejing Li; Qiang Xu; Jingwei Han; Jing Zhang; Ke Ren; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

A fungal polysaccharide from Trametes orientalis: Structural elucidation and multifaceted antitumor mechanisms via metastasis, angiogenesis, and immunomodulation - Wenrui He; Haojing Jiang; Mingming Rong; Xinxing Li; Jing Xu; Yuanqiang Guo (Carbohydrate Polymers, 2025)

O304 is a mitochondrial uncoupler which extends C. elegans lifespan and induces vasorelaxation of rat mesenteric arteries - Wen-Feng Li; Yi Zeng; Yi-Dan Zhang; Rong Zhang; Jing Lang; Wen-Jie Bu; Meng-Ke Zhao; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2025)

Climatological characteristics of tropical cyclones simulated in the global-regional integrated forecasting system (GRIST) model - Xi Cheng; Xinyao Rong; Yi Zhang; Yuqing Wang; Jian Li; Jing Xu (Climate Dynamics, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

The development of biological soil crusts shifts the drivers of soil multifunctionality in drylands - Mingming Wang; Boyi Song; Benfeng Yin; Ye Tao; Jing Zhang; Xiaoying Rong; Yonggang Li; Shihang Zhang; Zihan Kan; Yongxing Lu; Hao Guo; Xing Guo; et al. (CATENA, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Corrigendum to “Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression” [Toxicology 514 (2025) 154129] - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Regulatory measures for mitigating physical and mental health impacts in aerospace environment: A systematic review - Rong Liang; Jing Gao; Xiaohui Liu; Xinyao Li; Haonan Chang; Rongdian Yang; Jiajia Yang; Dong Ming (Life Sciences in Space Research, 2025)

Facile fabrication of ethyl cellulose/gelatin fibers incorporated with copper-based metal-organic frameworks as humidity-triggered release of carvacrol for blueberry preservation - Jing Xie; Xingyu Rong; Xiaoqian Jiang; Yuping Zhao; Tianhua Ding; Jing Yan; Suqing Li; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Tuning ligand defect in porphyrins metal-organic frameworks to boost electrochemiluminescence for sensitive detection of amyloid-β1-42 - Jinyan Li; Xiaoqi Pei; Rong Qu; Lei Liao; Wen Zhang; Zhen Wang; Gang Xie; Sanping Chen; Jing Han (Chemical Engineering Journal, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Algae-driven bacterial production of extracellular reactive oxygen species for emerging contaminants degradation - Xi Wang; Rong Ni; Lusen Li; Hongwei Yu; Jing Qi; Baiwen Ma; Chengzhi Hu; Jiuhui Qu (Science of The Total Environment, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Enhancing functional metabolites and antioxidant activity of a novel alternative kombucha-like beverage: Tailor-made symbiotic microbial consortium for apple juice fermentation - Shiqi Li; Rong Liu; Zhihuan Jing; Yaodong Guo; Zhouli Wang (Food Bioscience, 2025)

Metabolite analysis indicates role of flavones and free fatty acids in water deficit stress response of Cenchrus spinifex - Jing Cao; Zhensong Li; Thomas A. Monaco; Yuping Rong (Flora, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Optimization strategy for Cr(VI) removal in coke-based modular constructed wetlands: A comprehensive analysis of purification efficiency, removal mechanisms, and practical feasibility - Xinlu Xiao; Xuhao Li; Xiangling Zhang; Chen Wang; Xiaoting Liu; Jing Bai; Rong Zhang; Shilong Cao; Jiezhou Hu; Zhenchao Liu; Jun Shen (Journal of Environmental Management, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Triggered synergistic effect of Fe single atoms and tiny Co nanoparticles to enhanced oxygen electrocatalysis bifunctionality for zinc-air batteries - Jing Wu; Jian Rong; Chaohai Wang; Chaosheng Wang; Ning Fang; Yuzhe Zhang; Huaisheng Ao; Chao Jing; Yusuke Yamauchi; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Hydraulic and mechanical response of loess to different chemical components in root exudates - Rong Li; Chaobo Zhang; Siyu Zhang; Ruihan Jiang; Jing Jiang (Plant and Soil, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Environmental determinants of spatial-temporal variability in ammonia oxidizing microorganisms across diverse Chinese agricultural soils - Aiju Liu; Fangxu Rong; Guizhen Wang; Guoqin Hou; Jing Liu; Mingyue Li; Kai Liu; Zafran Gul Wazir; Hongliang Liu; Yuzhi Xu (Journal of Environmental Management, 2025)

The efficacy, safety, and persistence of vedolizumab versus adalimumab in patients with inflammatory bowel disease: a systematic review and meta-analysis - Zhixin Chen; Huo Li; Zhongzhuan Li; Rong Ouyang; Shijiang Huang; Shufen Qin; Jing Qin; Jiean Huang (Inflammopharmacology, 2025)

Assessment of Geostationary Satellite Cloud Effective Radius over East China with In Situ Aircraft Measurements - Qiuli Zhang; Chao Liu; Rong Zhang; Jing Yang; Junxia Li; Bo Li; Feng Lu; Yan Yin; Hongchun Jin (Journal of Meteorological Research, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Large-scale crop dataset and deep learning-based multi-modal fusion framework for more accurate G × E genomic prediction - Qixiang Zou; Shuaishuai Tai; Qianguang Yuan; Yating Nie; Heping Gou; Longfei Wang; Chuanxiu Li; Yi Jing; Fangchun Dong; Zhen Yue; Yi Rong; Xiaodong Fang; et al. (Computers and Electronics in Agriculture, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Epigenetic nanoplatform for synergistic immune activation and immunogenicity restoration enhancing cancer radio-immunotherapy - Zhenhu He; Xiaopei Peng; Jiong Li; Yaning Zhu; Xuan Zhang; Junhong Duan; Jing Ni; Mengtian Ma; Juan Wang; Zhenguo Liu; Bin Feng; Wenbin Zeng; et al. (Chemical Engineering Journal, 2025)

Nonradicals-dominated peroxymonosulfate activation of g-C3N4/CeO2 floating beads for enhanced inactivation of M. aeruginosa: Performance studies and mechanistic insights - Dandan Wang; Jing Li; Rong Zhang; Beiyu Xin; Xueru Huang; Yang Wang; Jifeng Guo (Chemical Engineering Journal, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanistic insights into efficient phosphorus adsorption and recovery from water using functional ZnO/ZnFe-LDHs alginate hydrogels - Shilong Cao; Xiangling Zhang; Shuqin Xie; Chen Wang; Jing Bai; Xuhao Li; Rong Zhang; Xinlu Xiao; Jiezhou Hu; Xiaoxia Jiang (Journal of Environmental Chemical Engineering, 2025)

Antibacterial chitosan/organic rectorite nanocomposite-conjugated gelatin/β-cyclodextrin hydrogels with improved hemostasis performance for wound repair - Rong Huang; Yongqian Bian; Wenxuan Wang; Lirong Xu; Hao Zhang; Haowei Zhou; Jincheng Du; Jiaqi Li; Yuheng Zhang; Xueyong Li; Jing Li (Carbohydrate Polymers, 2025)

PVA-enhanced green synthesis of CMC-based lithium adsorption films - Shengkai Liu; Huiling Li; Xi Li; Wei Wang; Chunguang Rong; Mengjie Yang; Yonggui Wang; Jing Wang; Yabei Xu; Daxin Liang; Yanjun Xie (Carbohydrate Polymers, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Methane seepage leads to a specific microplastic aging process in the simulated cold seep environment - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Bin Wang; Can-Rong Li; Yi-Lei Lin; Yong-Ji Huang; Song Zhong; Xiao-Chun Zhang; Jun-Lin Hu; Si Zhang (Journal of Hazardous Materials, 2025)

Effects of exposure to 17α-methyltestosterone on hepatic lipid metabolism in Gobiocypris rarus - Tongyao Li; Zijun Xiong; Weiya Rong; Qiong Yang; Yue Chen; Haiyan Zhao; Qing Liu; Jing Song; Weiwei Wang; Yu Liu; Xianzong Wang; Shaozhen Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Genetic Causal Association Between 15 Micronutrients and 12 Obstetric-Related Diseases: A Mendelian Randomization Study - Lele Pan; Jing Zhang; Mingwei Chen; Li Yuan; Rong Chen; Lina Zhao (Biological Trace Element Research, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Invisible hazards: Exploring neonicotinoid contamination and its environmental risks in urban parks across China - Yongfeng Deng; Ruqin Shen; Xue Zhang; Yang Li; Xingguo Chen; Rong-Rong He; Hao Tian; Shuqin Tang; Xiang Luo; Jing Li; Wan-Yang Sun; Hongli Tan (Science of The Total Environment, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Effect of zero-valent iron and magnetite on mitigating sulfate and lincomycin stress in anaerobic digestion: microbial succession and antibiotic resistant genes removal - Jing Xie; Jiaxin Zhu; Bolin Min; Rong He; Wenbiao Wang; Li Xie (Journal of Water Process Engineering, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Selective recovery of Au from waste printed circuit board by water-soluble organic leaching: The key role of in situ bromine mediation and identificationof pathway - Zhenfeng Xiong; Ying Huang; Yonghua Li; Changdong Sheng; Liwei Sun; Jing Ma; Baoyan Chi; Jiali Tan; Xiong Tang; Rong Zha; Xinhua Zhan (Journal of Hazardous Materials, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

MOF-derived S, N co-doped porous carbon matrix with single Fe atoms and CoSx nanoparticles dual-sites for enhanced oxygen reduction - Yu chen; Jian Rong; Jing Wu; Yuzhe Zhang; Huaisheng Ao; Xudong Zheng; Chao Jing; Ruilan Yang; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Improved global estimation of seasonal variations in C3 photosynthetic capacity based on eco-evolutionary optimality hypotheses and remote sensing - Yihong Liu; Jing M. Chen; Mingzhu Xu; Rong Wang; Weiliang Fan; Wenyu Li; Lucas Kammer; Colin Prentice; Trevor F. Keenan; Nicholas G. Smith (Remote Sensing of Environment, 2024)

Genomic analysis of hypoxia-tolerant population of the Chinese mitten crab (Eriocheir sinensis) - Feng-yuan Yan; Yuan-feng Xu; Wen-rong Feng; Qing-hong He; Guo-an Hua; Wen-jing Li; Pao Xu; Jun Zhou; Yong-kai Tang (Fish & Shellfish Immunology, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

PoIL8-L, a teleost interleukin-8 like, enhances leukocyte cellular vitality and host defense against bacterial infections in Japanese flounder (Paralichthys olivaceus) - Kun-yu Zhao; Yue Fang; Rong-jing Xu; Jian Zhang; Bin Sun; Xue-peng Li (Fish & Shellfish Immunology, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Effects of low-temperature stress on serum biochemical indicators, intestinal microbiome, and transcriptome of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Aquaculture International, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Elevational distribution of forests and its spatiotemporal dynamics in subtropical China from 2000 to 2019 - Zhencan Zheng; Liuwen Zhuang; Guofang Miao; Han Liu; Zhiqiang Cheng; Wenyu Li; Rong Shang; Peng Gong; Jing Ming Chen (Science China Earth Sciences, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Long-term residue returning increased subsoil carbon quality in a rice-wheat cropping system - Yinan Xu; Yalin Yu; Jing Sheng; Yuekai Wang; Haishui Yang; Feng-Min Li; Shiping Liu; Zheng-Rong Kan (Journal of Environmental Management, 2024)

Effects of carnosine combined with Lactobacillus on the antioxidant capacity of liver and kidney in normal or stressed mice - Jian Qin; Yue Ma; Conghui Wang; Huiying Li; Zhiqiang Zou; Yunqing Zhang; Jing Ma; Rong Du (Food Bioscience, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Efficient turn-on fluorescent probe cooperated by cascade response for disclosing the fluctuation of cysteine in cells - Li Meng; Zi Yi Xu; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Analytica Chimica Acta, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Responses of phenology to preseason drought and soil temperature for different land cover types on the Mongolian Plateau - Bing Li; Rong Wang; Jing M. Chen (Science of The Total Environment, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Underlying the inhibition mechanisms of sulfate and lincomycin on long-term anaerobic digestion: Microbial response and antibiotic resistance genes distribution - Li Xie; Jiaxin Zhu; Jing Xie; Jun Xu; Rong He; Wenbiao Wang (Science of The Total Environment, 2024)

Effects of combined exposure to polystyrene microplastics and 17α-Methyltestosterone on the reproductive system of zebrafish - Weiya Rong; Yue Chen; Zijun Xiong; Haiyan Zhao; Tongyao Li; Qing Liu; Jing Song; Xianzong Wang; Yu Liu; Shaozhen Liu (Theriogenology, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Automatic and adaptive picking of surface-wave dispersion curves for near-surface application - Hui Liu; Jing Li; Rong Hu (Journal of Applied Geophysics, 2024)

A study of volatiles of young citrus fruits from four areas based on GC–MS and flash GC e-nose combined with multivariate algorithms - Qian Zhang; Rong Xue; Xi Mei; Lianlin Su; Wei Zhang; Yu Li; Jinguo Xu; Jing Mao; Chunqin Mao; Tulin Lu (Food Research International, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

Exploring carbon content variation in microplastics sequestrated from seawater to sediment in the Haima cold seep area - Xiao-Nan Wu; Jing-Chun Feng; Xiao Chen; Can-Rong Li; Si Zhang (Journal of Hazardous Materials, 2024)

Direct and indirect photodegradation of bisphenol A in the presence of natural water components - Yao Han; Lijun Li; Lu Jin; Rong Zhou; Yayu Li; Weiwen Jing (Environmental Geochemistry and Health, 2024)

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

Driving model of land use change on the evolution of carbon stock: a case study of Chongqing, China - Luoshan Zheng; Yangbing Li; Yan Chen; Rong Wang; Shijie Yan; Chunhua Xia; Bing Zhang; Jing’an Shao (Environmental Science and Pollution Research, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Orthodontic craniofacial pattern diagnosis: cephalometric geometry and machine learning - Yuqing Zhou; Bochun Mao; Jiwu Zhang; Yanheng Zhou; Jing Li; Qiguo Rong (Medical & Biological Engineering & Computing, 2023)

Morphological and Pull-Out Mechanical Properties of Alfalfa Roots in the Seedling Stage - Chaobo Zhang; Rong Li; Jing Jiang; Qihong Yang (Journal of Soil Science and Plant Nutrition, 2023)

Effects of Different Conditioners on Humus Composition and Humic Acid Structural Characteristics in Black Soil Under the Combined Application of Pig Manure and Straw - Shuang Zheng; Jing-Gui Wu; Jin-Rong Li; Juan Hu; Li He (Journal of Soil Science and Plant Nutrition, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Experimental infection and co-infection with Chinese strains of Ehrlichia canis and Babesia vogeli in intact and splenectomized dogs: Insights on clinical, hematologic and treatment responses - Jilei Zhang; Jiawei Wang; Patrick John Kelly; Yuanyuan Zhang; Min Li; Jing Li; Rong Zhang; Yaoyao Wang; Ke Huang; Jinfeng You; Haixiang Qiu; Xiaofeng Zheng; et al. (Veterinary Parasitology, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Soil microbial diversity and network complexity sustain ecosystem multifunctionality following afforestation in a dry-hot valley savanna - Shuaifeng Li; Xiaobo Huang; Rong Tang; Jing Li; Biao Zhu; Jianrong Su (CATENA, 2023)

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

Impact of nitrogen addition on single and mixed tree leaf litter decomposition depends on N forms in subtropical China - Pan-Pan Wu; Zao Zhang; Rui Li; Jing-Hao Ji; Rong Mao (Applied Soil Ecology, 2023)

Hypervirulent Klebsiella pneumoniae detection methods: a minireview - Qi-bin Zhang; Peng Zhu; Shun Zhang; Yan-jing Rong; Zuo-an Huang; Li-wan Sun; Ting Cai (Archives of Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Microbial network complexity and diversity together drive the soil ecosystem multifunctionality of forests during different woodland use intensity in dry and wet season - Jing Li; Xiaobo Huang; Shuaifeng Li; Rong Tang; Jianrong Su (Forest Ecology and Management, 2023)

Involvement of Abnormal p-α-syn Accumulation and TLR2-Mediated Inflammation of Schwann Cells in Enteric Autonomic Nerve Dysfunction of Parkinson’s Disease: an Animal Model Study - Wenwen Jiang; Yue Cheng; Ye Wang; Jing Wu; Zhe Rong; Li Sun; Yan Zhou; Kezhong Zhang (Molecular Neurobiology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Deciphering riverine dissolved organic matter biodegradation: Evidence from three-dimensional fluorescence - Rong Xu; Jing Zhang; Jianwei Li; Rui Liu; Maofei Ni; Guangneng Zeng (Journal of Environmental Chemical Engineering, 2023)

Removal of iodide anions in water by silver nanoparticles supported on polystyrene anion exchanger - Li Li; Su-Juan Yu; Rong-Gang Zheng; Peng Li; Qing-Cun Li; Jing-Fu Liu (Journal of Environmental Sciences, 2023)

Differential Diagnosis of DCIS and Fibroadenoma Based on Ultrasound Images: a Difference-Based Self-Supervised Approach - Jin Yin; Jia-Jun Qiu; Jing-Yan Liu; Yi-Yue Li; Qi-Cheng Lao; Xiao-Rong Zhong; Mengling Feng; Hao Du; Shao-Liang Peng; Yu-Lan Peng (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Proteomics Analysis of Lipid Metabolism and Inflammatory Response in the Liver of Rabbits fed on a High Cholesterol Diet - Jing Wu; Wei-Hua Li; Wei-Rong Wang; Xue-Qin Jin; En-Qi Liu (Cell Biochemistry and Biophysics, 2023)

Linear and nonlinear interface rheological behaviors and structural properties of pea protein (vicilin, legumin, albumin) - Qian Shen; Jing Li; Xiaojun Shen; Xinyu Zhu; Jun Dai; Cuie Tang; Rong Song; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Does carbon emission trading mitigate firm's default risk? Evidence from China - Qingjun Zhang; Sulan Zhang; Rong Chen; Jing Li (Journal of Cleaner Production, 2023)

Controllable Pd@Cu2O Schottky junction interface with improved anti-poisoning effect for efficiently electroreduction of CO2 into syngas - Rong Cai; Xin Du; Guorui Liu; Xiuli Wang; Qiang Tang; Xinpin Pan; Feng Li; Jing Li (Fuel, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Global photosynthetic capacity of C3 biomes retrieved from solar-induced chlorophyll fluorescence and leaf chlorophyll content - Yihong Liu; Jing M. Chen; Liming He; Rong Wang; Nicholas G. Smith; Trevor F. Keenan; Cheryl Rogers; Wenyu Li; Jiye Leng (Remote Sensing of Environment, 2023)

Effects of low-temperature stress on intestinal structure, enzyme activities and metabolomic analysis of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Frontiers in Marine Science, 2023)
Water temperature plays a crucial role in the growth, survival, and reproduction of fish species, as they make up the majority of aquatic fauna. In this study, the effects of low temperature were studied on the functional state of juvenile golden pompano ( Trachinotus ovatus ) under low-temperature stress. The study was conducted at 28°C in the control group and 18°C in the cold group for 14 d to determine the intestinal tissue, digestive and antioxidant enzyme activities, and metabolites of juvenile fish. The results showed that: (1) the swelling degree of the muscle layer deepened and was congested with a longer low-temperature stress period. The folds were sparse, from slight swelling to shedding and deformation. The intestinal mucosa was necrotic and had vacuoles, and the number gradually increased. Serious erosion of the villi occurred. (2) The specific activities of digestive enzymes showed a downward trend. (3) The intestinal superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, and glutathione peroxidase (GSH-Px) activity showed an upward trend. The intestinal catalase (CAT) activity showed a downward trend. (4) Compared with the control group, there were 28 metabolites in the cold group showing significant differences, among which Z, 11Z, 14Z-eicosatrienoic acid, stearic acid, and adrenic acid showed an upward trend. In contrast, spermidine and uracil showed a downward trend. Among the enriched metabolic pathways, the main differential pathways were unsaturated fatty acid biosynthesis, fatty acid biosynthesis, linoleic acid metabolism, pyrimidine metabolism, and β-alanine metabolism. According to metabolomic analysis, under low-temperature stress, the fish body improved the synthesis of unsaturated fatty acids and saturated fatty acids to adapt to a low-temperature environment and consumed spermidine to improve its immune ability to clear the peroxide generated by the synthesis of unsaturated fatty acids in the body so that the cells were protected from oxidative damage. After 14 days, low-temperature stress affected metabolites and enzyme activity indices in juvenile golden pompano. Low-temperature stress causes changes in intestinal antioxidants and digestive enzymes and damage intestinal tissues. As a result of this exploration of how low temperatures affect the juvenile golden pompano, the foundation is laid for future studies, such as the molecular mechanisms of low-temperature adaptation in fish species.

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Four new glycosides from Gerbera piloselloides - Ha Gao; Chen-Xu Zhao; Xin-Yao Luo; Jing-Rong Li; Xiao-Chuan Ye; Tao Zhang; Zhong-Mei Zou (Phytochemistry Letters, 2023)

Diagnosis of atmospheric circulation shifts in the central Tibetan Plateau: Evidence from stable isotopes - Yao Li; Wusheng Yu; Lide Tian; Stephen Lewis; Kei Yoshimura; Cheng Wang; Jiangpeng Cui; Yaoming Ma; Rong Guo; Jingyi Zhang; Zhaowei Jing; Lili Shao; et al. (Atmospheric Research, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Insights into the accumulation, distribution and toxicity of pyrene associated with microplastics in rice (Oryza sativa L.) seedlings - Lili Tian; Li Ya Ma; Xiaolong Chen; Jing Ge; Yini Ma; Rong Ji; Xiangyang Yu (Chemosphere, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

A ca. 290 Ma hydrothermal calcite in Cambrian dolostone - Zhongwu Lan; Shitou Wu; Fangyue Wang; Bo Liu; Kaibo Shi; Jing Sun; Rong Cao; Xian-Hua Li (Marine and Petroleum Geology, 2023)

Foaming and interfacial properties of desalted duck egg white nanogels after weak enzymatical hydrolyzation - Bin Zhou; Jingyun Zhao; Yujuan Rong; Mengchen Li; Hongshan Liang; Bin Li; Jing Sun (Food Hydrocolloids, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

Nitric Oxide Enhances Salt Tolerance in Tomato Seedlings by Regulating Endogenous S-nitrosylation Levels - Chunlei Wang; Lijuan Wei; Jing Zhang; Dongliang Hu; Rong Gao; Yayu Liu; Li Feng; Wenting Gong; Weibiao Liao (Journal of Plant Growth Regulation, 2023)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Recognition of the Multi-class Schizophrenia Based on the Resting-State EEG Network Topology - Fali Li; Lin Jiang; Yuanyuan Liao; Cunbo Li; Qi Zhang; Shu Zhang; Yangsong Zhang; Li Kang; Rong Li; Dezhong Yao; Gang Yin; Peng Xu; et al. (Brain Topography, 2022)

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

Asymmetric changes of photosynthetically active radiation and light utilization efficiency during the maize growing season in North China - Huayun He; Qi Hu; Jing Wang; Mengyuan Xing; Yuanyuan Liu; Xiaochen Wang; Rong Li; Xuebiao Pan; Zhihua Pan; Binxiang Huang; Qijin He (Theoretical and Applied Climatology, 2022)

γ-Cyclodextrin metal–organic framework as a carrier to deliver triptolide for the treatment of hepatocellular carcinoma - Zhe Li; Gang Yang; Rong Wang; Yuanyuan Wang; Jing Wang; Meng Yang; Chunai Gong; Yongfang Yuan (Drug Delivery and Translational Research, 2022)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Understanding the key factors determining rural domestic waste treatment behavior in China: a meta-analysis - Donghui Zheng; Jing Shen; Rong Li; Bei Jian; Jihong Zeng; Yongliang Mao; Xiaoning Zhang; Pradipta Halder; Mei Qu (Environmental Science and Pollution Research, 2022)

Association Between Essential Metal Elements and the Risk of Autism in Chinese Han Population - Jiahui Ma; Jing Wu; Haibin Li; Jingyu Wang; Jisheng Han; Rong Zhang (Biological Trace Element Research, 2022)

Regulation of β1-integrin in autophagy and apoptosis of gastric epithelial cells infected with Helicobacter pylori - Boqing Li; Qianyu Rong; Yunqiu Du; Ruiqing Zhang; Jing Li; Xiaohan Tong; Li Geng; Ying Zhang (World Journal of Microbiology and Biotechnology, 2022)

Tree mycorrhizal effect on litter-leached DOC amounts and biodegradation is highly dependent on leaf habits in subtropical forests of southern China - Yi-Dong Ding; Xin-Yi Xie; Jing-Hao Ji; Qian-Qian Li; Jia-Wen Xu; Rong Mao (Journal of Soils and Sediments, 2021)

Effects of drought and heat on the productivity and photosynthetic characteristics of alpine meadow plants on the Qinghai-Tibetan Plateau - Li Ma; Zhong-hua Zhang; Bu-qing Yao; Zhen Ma; Xiao-tao Huang; Bing-rong Zhou; Man-hou Xu; Jing Guo; Hua-kun Zhou (Journal of Mountain Science, 2021)

Cooperation Search Algorithm for Power Generation Production Operation Optimization of Cascade Hydropower Reservoirs - Wen-jing Niu; Zhong-kai Feng; Yu-rong Li; Shuai Liu (Water Resources Management, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Dietary Supplementation with Sea Cucumber Saponins and Exercise Can Significantly Suppress Adipose Accumulation in Mice Fed with High-Fat Diet - Rong Li; Jing Meng; Haohao Shi; Chengcheng Wang; Zhaojie Li; Changhu Xue; Yuming Wang; Tiantian Zhang (Journal of Ocean University of China, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Effect of bFGF on fibroblasts derived from the golden snub-nosed monkey - Xin Liu; Hao Wei; Jing Yang; Jingjing Li; Pei Zhang; Yuli Li; Rong Hou; Jinlian Hua; Xingrong Yan; Baoguo Li (Primates, 2021)

Prenatal Stress Leads to the Altered Maturation of Corticostriatal Synaptic Plasticity and Related Behavioral Impairments Through Epigenetic Modifications of Dopamine D2 Receptor in Mice - Yingchun Li; Jing Rong; Haiquan Zhong; Min Liang; Chunting Zhu; Fei Chang; Rong Zhou (Molecular Neurobiology, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Patterns of intrinsic brain activity in essential tremor with resting tremor and tremor-dominant Parkinson’s disease - Jun-ying Li; Zhong-jiao Lu; Xue-ling Suo; Nan-nan Li; Du Lei; Ling Wang; Jia-xin Peng; Li-ren Duan; Jing Xi; Yi Jiang; Qi-yong Gong; Rong Peng (Brain Imaging and Behavior, 2020)

Influence of soil moisture content on pullout properties of Hippophae rhamnoides Linn. roots - Chao-bo Zhang; Ya-ting Liu; Dong-rong Li; Jing Jiang (Journal of Mountain Science, 2020)

NLRP6 contributes to inflammation and brain injury following intracerebral haemorrhage by activating autophagy - Han Xiao; Hui Chen; Rong Jiang; Li Zhang; Lu Wang; Hui Gan; Ning Jiang; Jing Zhao; Xuan Zhai; Ping Liang (Journal of Molecular Medicine, 2020)

Ferulic Acid Ameliorates MPP+/MPTP-Induced Oxidative Stress via ERK1/2-Dependent Nrf2 Activation: Translational Implications for Parkinson Disease Treatment - Xu Li; Jing Zhang; Hua Rong; Xiaojie Zhang; Miaoxian Dong (Molecular Neurobiology, 2020)

Bergaptol, a mechanism-based inactivator of CYP2C9 - Tingting Jiang; Ting Cheng; Jing Li; Mengyue Zhou; Rong Tan; Xiaojing Yang; Yang Wang; Weiwei Li; Jiang Zheng (Medicinal Chemistry Research, 2020)

Circular RNA hsa_circ_0002052 promotes osteosarcoma via modulating miR-382/STX6 axis - Ping-rong Zhang; Jing Ren; Jian-shan Wan; Rong Sun; Ying Li (Human Cell, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

Prevalence of RNF213 variants in symptomatic intracranial arterial stenosis/occlusion in China - Xunsha Sun; Man Luo; Jiaoxing Li; Rong Lai; Jing Lin; Yufang Wang; Xiaowei Xu; Shaoqing Wu; Wenli Sheng (Molecular Genetics and Genomics, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Novel 28 microsatellite loci using high-throughput sequencing for an endangered species on Metasequoia glyptostroboides (Cupressaceae) - Jing-Wen Wang; Tong-Lei Xu; Ghenet Weldegebriel Sereke; Rong Wang; Yuan-Yuan Li (Molecular Biology Reports, 2020)

Predictors of nasal bacterial culture rates in patients with chronic rhinosinusitis - Jing-Jie Wang; Chih-Yi Chen; Kai-Li Liang; Rong-San Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evidence of compliance with and effectiveness of guidelines for noninvasive prenatal testing in China: a retrospective study of 189,809 cases - Chan Tian; Tao Deng; Xiuhuang Zhu; Chen Gong; Yangyu Zhao; Yuan Wei; Rong Li; Xiufeng Xu; Miaonan He; Zhiwei Zhang; Jing Cheng; Mol BenWillem; et al. (Science China Life Sciences, 2020)

Effect of different seasons (spring vs summer) on the microbiota diversity in the feces of dairy cows - Han Li; Rong Li; Huijun Chen; Jing Gao; Yu Wang; Yifeng Zhang; Zhili Qi (International Journal of Biometeorology, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Interaction Between Planetary Boundary Layer and PM2.5 Pollution in Megacities in China: a Review - Yucong Miao; Jing Li; Shiguang Miao; Huizheng Che; Yaqiang Wang; Xiaoye Zhang; Rong Zhu; Shuhua Liu (Current Pollution Reports, 2019)
Purpose of Review During the past decades, the number and size of megacities have been growing dramatically in China. Most of Chinese megacities are suffering from heavy PM 2.5 pollution. In the pollution formation, the planetary boundary layer (PBL) plays an important role. This review is aimed at presenting the current state of understanding of the PBL-PM 2.5 interaction in megacities, as well as to identify the main gaps in current knowledge and further research needs. Recent Findings The PBL is critical to the formation of urban PM 2.5 pollution at multiple temporal scales, ranging from diurnal change to seasonal variation. For the essential PBL structure/process in pollution, the coastal megacities have different concerns from the mountainous or land-locked megacities. In the coastal cities, the recirculation induced by sea-land breeze can accumulate pollutants, whereas in the valley/basin, the blocking effects of terrains can lead to stagnant conditions and thermal inversion. Within a megacity, although the urbanization-induced land use change can cause thermodynamic perturbations and facilitate the development of PBL, the increases in emissions outweigh this impact, resulting in a net increase of aerosol concentration. Moreover, the aerosol radiative effects can modify the PBL by heating the upper layers and reducing the surface heat flux, suppressing the PBL and exacerbating the pollution. Summary This review presented the PBL-PM 2.5 interaction in 13 Chinese megacities with various geographic conditions and elucidated the critical influencing processes. To further understand the complicated interactions, long-term observations of meteorology and aerosol properties with multi-layers in the PBL need to be implemented.

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

EEG-based mild depression recognition using convolutional neural network - Xiaowei Li; Rong La; Ying Wang; Junhong Niu; Shuai Zeng; Shuting Sun; Jing Zhu (Medical & Biological Engineering & Computing, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

Synthesis, antitumor evaluation and molecular docking study of a novel podophyllotoxin-lonidamine hybrid - Lei Zhang; Jie Zheng; Ying Rong; Chengli Yang; Li Long; Yingshu Xu; Yongzheng Chen; Jing Wang; Qizheng Yao (Medicinal Chemistry Research, 2018)

The complete mitochondrial genome of an endangered reef gastropods Trochus pyramis - Zhi-ying Zhao; Zhi-gang Tu; Jing Cui; Li-rong Bai (Conservation Genetics Resources, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Effects of probiotic on microfloral structure of live feed used in larval breeding of turbot Scophthalmus maximus - Yan Jiang; Zheng Zhang; Yingeng Wang; Yayun Jing; Meijie Liao; Xiaojun Rong; Bin Li; Guiping Chen; Hesen Zhang (Journal of Oceanology and Limnology, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Supplementation with turmeric residue increased survival of the Chinese soft-shelled turtle (Pelodiscus sinensis) under high ambient temperatures - Yong Chen; Yi-fan Zhang; Hao-cheng Qian; Jing-liang Wang; Zhe Chen; Jose M. Ordovas; Chao-qiang Lai; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2018)

Characterization of an endangered marine strombid gastropod Strombus luhuanus complete mitochondrial genome - Zhi-ying Zhao; Zhi-gang Tu; Li-rong Bai; Jing Cui (Conservation Genetics Resources, 2018)

Study on the influential biochemical indices of Cd(II) on Eisenia fetida in oxidative stress by principal component analysis in the natural soil - Yucui Ning; Liyan Liu; Guohua Rong; Xu Cao; Jing Li; Ye Su; Dongxing Zhou (Environmental Science and Pollution Research, 2018)

Exploration of the formation mechanism and source attribution of ambient ozone in Chongqing with an observation-based model - Rong Su; KeDing Lu; JiaYan Yu; ZhaoFeng Tan; MeiQing Jiang; Jing Li; ShaoDong Xie; YuSheng Wu; LiMin Zeng; ChongZhi Zhai; YuanHang Zhang (Science China Earth Sciences, 2018)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Enhanced delivery of biodegradable mPEG-PLGA-PLL nanoparticles loading Cy3-labelled PDGF-BB siRNA by UTMD to rat retina - Jing Du; Ying Sun; Feng-Hua Li; Lian-Fang Du; You-Rong Duan (Journal of Biosciences, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

The effect of light on the cellular stoichiometry of Chlorella sp. in different growth phases: implications of nutrient drawdown in batch experiments - Jing Liu; Zhe Li; Jing-song Guo; Yan Xiao; Fang Fang; Rong-cong Qin; Ling-ling Zhang (Journal of Applied Phycology, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Dynamic failure mode and energy-based identification method for a counter-bedding rock slope with weak intercalated layers - Gang Fan; Jian-jing Zhang; Xiao Fu; Li-rong Zhou (Journal of Mountain Science, 2016)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

De novo transcriptome sequencing of Acer palmatum and comprehensive analysis of differentially expressed genes under salt stress in two contrasting genotypes - Liping Rong; Qianzhong Li; Shushun Li; Ling Tang; Jing Wen (Molecular Genetics and Genomics, 2016)

Evaluation of a water-soluble adjuvant for the development of monoclonal antibodies against small-molecule compounds - Rui Liu; Ying Liu; Mei-jing Lan; Niusha Taheri; Jing-li Cheng; Yi-rong Guo; Guo-nian Zhu (Journal of Zhejiang University-SCIENCE B, 2016)

The effect of different genome and cytoplasm on meiotic pairing in maize newly synthetic polyploids - Mingjun Cheng; Mingmin Zheng; Shipeng Yang; Yang Li; Xingchun Dong; Jing Li; Rulong Sun; Huaxiong Li; Shufeng Zhou; Yuanqi Wu; Tingzhao Rong; Qilin Tang (Euphytica, 2016)
Allopolyploidization plays the special role in the evolution of many crops. Moreover, the evolution in early stage of some allopolyploidization events is predicted to be effected by nuclear-cytoplasmic interactions. Maize and teosintes are well model system for study of genetic recombination in allopolyploidization. In order to investigate the effects of genome organization and cytoplasm on genome evolution in newly synthesized allopolyploids (neoallopolyploids), a series of neoallopolyploids were produced by reciprocal crosses of maize and Zea perennis . By using dual-color genomic in situ hybridization, intra- and intergenomic meiosis pairing of these polyploids were quantified and compared with regard to its genome organization and cytoplasm background. In the four neoallopolyploids, the stability of maize genome is consistently lower than that of Z. perennis genome. Additional, the stability of maize genome is affected by genome ploidy. The cytoplasm, genome composition and their interaction do have the special role in chromosome paring and the meiosis behaviors in Zea allopolyploids vary significantly and showed non-diploidization. Z. perennis cytoplasm may give a relatively relaxed environment for maize genome.

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Age-related changes in photosynthesis and water relations of revegetated Caragana korshinskii in the Tengger desert, Northern China - Jing-Ting Bao; Jin Wang; Xin-Rong Li; Zhi-Shan Zhang; Jie-Qiong Su (Trees, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

Luteolin attenuate the d -galactose-induced renal damage by attenuation of oxidative stress and inflammation - Yuqing Xu; Jingzheng Zhang; Jing Liu; Sai Li; Cheng Li; Wen Wang; Rong Ma; Yi Liu (Natural Product Research, 2015)

Different influences of field aging on nickel toxicity to Folsomia candida in two types of soil - Yu-Rong Liu; Jing Li; Ji-Zheng He; Yi-Bing Ma; Yuan-Ming Zheng (Environmental Science and Pollution Research, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Multilocus sequence typing analysis of Cronobacter spp. isolated from China - Jing-Hua Cui; Xiao-Li Du; Rong-Jie Wei; Hai-Jian Zhou; Wei Li; Stephen Forsythe; Zhi-Gang Cui (Archives of Microbiology, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

The Effect of Continuous Blood Purification on the Prognosis of Cardiorenal Syndrome Patients - Fengyu Jia; Peng Rong; Dandan Li; Suxia Wang; Ying Jing; Yanming Ge; Jianzhong Meng (Cell Biochemistry and Biophysics, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Separation of the impact of climate change and human activity on streamflow in the upper and middle reaches of the Taoer River, northeastern China - Bin Li; Hongbo Su; Fang Chen; Haibin Li; Renhua Zhang; Jing Tian; Shaohui Chen; Yongming Yang; Yuan Rong (Theoretical and Applied Climatology, 2014)

Studies on the analgesic activities of Jia-Yuan-Qing pill and its safety evaluation in mice - Ye Tian; Li-rong Teng; Jing-jing Song; Qing-fan Meng; Jia-hui Lu; Wei-wei Zhang; Kang Wei; Ning Wang; Di Wang; Le-sheng Teng (Protoplasma, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Neuroglobin Promotes Neurite Outgrowth via Differential Binding to PTEN and Akt - Li Li; Qian Rong Liu; Xin Xin Xiong; Ju Mei Liu; Xiao Jing Lai; Chun Cheng; Feng Pan; Yong Chen; Shang Bin Yu; Albert Cheung Hoi Yu; Xiao Qian Chen (Molecular Neurobiology, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Overexpression of the AtSTK gene increases salt, PEG and ABA tolerance in Arabidopsis - Lei Bing; Cui-Cui Feng; Jing-Lan Li; Xiao-Xu Li; Bao-Cun Zhao; Yin-Zhu Shen; Zhan-Jing Huang; Rong-Chao Ge (Journal of Plant Biology, 2013)

Rhynchophylline-induced vasodilation in human mesenteric artery is mainly due to blockage of L-type calcium channels in vascular smooth muscle cells - Peng-Yun Li; Xiao-Rong Zeng; Jun Cheng; Jing Wen; Isao Inoue; Yan Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Prostaglandin E2 receptor EP1 phosphorylate CREB and mediates MMP2 expression in human cholangiocarcinoma cells - Bo Sun; Rong Rong; Hai Jiang; Hai Zhang; YiPin Wang; Xiaoming Bai; Min Zhang; Juan Ma; Shukai Xia; Wei Shu; Li Zhang; Jing Leng (Molecular and Cellular Biochemistry, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Decreased PADI4 mRNA Association with Global Hypomethylation in Hepatocellular Carcinoma During HBV Exposure - Changsong Zhang; Lieying Fan; Tingting Fan; Dong Wu; Lu Gao; Yang Ling; Jing Zhu; Rong Li; Lixin Wei (Cell Biochemistry and Biophysics, 2013)

The changing pattern of droughts in the Lancang River Basin during 1960–2005 - Bin Li; Hongbo Su; Fang Chen; Shenggong Li; Jing Tian; Yuchu Qin; Renhua Zhang; Shaohui Chen; Yongming Yang; Yuan Rong (Theoretical and Applied Climatology, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

Rapid odor perception in rat olfactory bulb by microelectrode array - Jun Zhou; Qi Dong; Liu-jing Zhuang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Benfotiamine prevents increased β-amyloid production in HEK cells induced by high glucose - Xiao-Jing Sun; Lei Zhao; Na Zhao; Xiao-Li Pan; Guo-Qiang Fei; Li-Rong Jin; Chun-Jiu Zhong (Neuroscience Bulletin, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Molecular and morphological studies of Paecilomyces sinensis reveal a new clade in clavicipitaceous fungi and its new systematic position - Wen-Jing Wang; Xiao-Liang Wang; Yi Li; Sheng-Rong Xiao; Ryan M. Kepler; Yi-Jian Yao (Systematics and Biodiversity, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

Effects of Atorvastatin on Pathological Changes in Brain Tissue and Plasma MMP-9 in Rats with Intracerebral Hemorrhage - Jing-Jing Cui; Dong Wang; Fei Gao; Yue-Rong Li (Cell Biochemistry and Biophysics, 2012)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

The Development and Stability of the Genus Bacteriodes from Human Gut Microbiota in HFA Mice Model - Jing Yuan; Benhua Zeng; Rong Niu; Huan Tang; Wenxia Li; Zhixue Zhang; Hong Wei (Current Microbiology, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Sequence Analysis of the Lactoferrin Gene and Variation of g.7605C→T in 10 Chinese Indigenous Goat Breeds - Jing-Fen Kang; Xiang-Long Li; Hui-Qin Zheng; Rong-Yan Zhou; Lan-Hui Li; Hong-Yuan Zhao (Biochemical Genetics, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Seismic analysis of the active character of the Taihang Mountain piedmont fault - Ming-Cai Xu; Jing-Hua Gao; Li-Xin Rong; Guang-Ke Wang; Xiao-Jiang Wang (Applied Geophysics, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Spectroscopic Studies on the Binding of Cobalt(II) 1,10-Phenanthroline Complex to Bovine Serum Albumin - Ye-Zhong Zhang; Hua-Rong Li; Jie Dai; Wen-Juan Chen; Jing Zhang; Yi Liu (Biological Trace Element Research, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Sequencing of Part of the Goat agouti Gene and SNP Identification - Xiang-long Li; Jing-wen Zhao; Chun-juan Tang; Rong-yan Zhou; Guiru Zheng; Lan-hui Li; Xiu-li Guo (Biochemical Genetics, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Erratum to: Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2009)

Cloning and functional analysis of wheat V-H+-ATPase subunit genes - Qian Zhao; Yan-Jun Zhao; Bao-Cun Zhao; Rong-Chao Ge; Ming Li; Yin-Zhu Shen; Zhan-Jing Huang (Plant Molecular Biology, 2009)

Distribution, biomass, and dynamics of roots in a revegetated stand of Caragana korshinskii in the Tengger Desert, northwestern China - Zhi-Shan Zhang; Xin-Rong Li; Li-Chao Liu; Rong-Liang Jia; Jing-Guang Zhang; Tao Wang (Journal of Plant Research, 2009)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Characterizing and estimating rice brown spot disease severity using stepwise regression, principal component regression and partial least-square regression - Zhan-yu Liu; Jing-feng Huang; Jing-jing Shi; Rong-xiang Tao; Wan Zhou; Li-li Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Phenolic constituents from the rhizomes of Gastrodia elata - Xiao-Dong Yang; Jie Zhu; Rong Yang; Jing-Ping Liu; Liang Li; Hong-Bin Zhang (Natural Product Research, 2007)

Pharmacokinetics of three proton pump inhibitors in Chinese subjects in relation to the CYP2C19 genotype - Hai-Ling Qiao; Yu-Rong Hu; Xin Tian; Lin-Jing Jia; Na Gao; Li-Rong Zhang; Yu-Zhong Guo (European Journal of Clinical Pharmacology, 2006)

The chirality selectivity in the uptake of platinum (II) complexes with 1,2-cyclohexanediamine isomers as carrier ligand by human erythrocytes - Juan Zou; Xiao Gai Yang; Rong Chang Li; Jing Fen Lu; Kui Wang (BioMetals, 1997)